2009
DOI: 10.1007/s10903-009-9256-5
|View full text |Cite
|
Sign up to set email alerts
|

Severe Malaria in Immigrant Population: A Retrospective Review

Abstract: Imported malaria continues to be an increasing medical challenge in the US. A significant proportion of imported malaria occurs in foreign born immigrants visiting their native countries and do not take prophylaxis for malaria mostly due to a misconception of being immune to malaria. The purpose of this study is to review epidemiology, clinical presentation, rate of prophylaxis and delineate the rate of severe malaria in a community hospital with largely immigrant population. Retrospective chart review of fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Imported malaria in France accounts for 50% of all imported malaria in Europe, and trends show a rise in the proportion of malaria patients with origins in sub-Saharan Africa who live in France and visit family and friends in their country of origin (7). Similar reports come from the United States, indicating that VFRs are among those most affected by imported malaria, which was acquired mostly in West Africa (24,25). Such findings are reflected by the intense malaria transmission in sub-Saharan African countries and patterns of travel between Africa and nonendemic settings (1,8,26).…”
Section: Epidemiology Of Imported Malaria Global Epidemiologymentioning
confidence: 86%
“…Imported malaria in France accounts for 50% of all imported malaria in Europe, and trends show a rise in the proportion of malaria patients with origins in sub-Saharan Africa who live in France and visit family and friends in their country of origin (7). Similar reports come from the United States, indicating that VFRs are among those most affected by imported malaria, which was acquired mostly in West Africa (24,25). Such findings are reflected by the intense malaria transmission in sub-Saharan African countries and patterns of travel between Africa and nonendemic settings (1,8,26).…”
Section: Epidemiology Of Imported Malaria Global Epidemiologymentioning
confidence: 86%
“…Prevalence of P. vivax or P. falciparum among migrants in previously published reports [4][5][6][7] is variable according to the origin of migrants, P. falciparum being more frequent than P. vivax among migrants from sub-Saharan Africa than among those from Latin America. In our case series, P. vivax malaria was present in all.…”
Section: Discussionmentioning
confidence: 99%
“…P. vivax is known to be more common among migrants from Latin America (Table 1), and as in other case series, we found that migrants were young, with lower comorbidity, a lower proportion of severe malaria and similar clinical findings. [4][5][6][7] Interestingly, none of the malaria cases come from the Bolivar state, where Venezuelan malaria has been particularly frequent in recent years from internal migration for the purpose of gold-mining. 1 Despite the limitations of a retrospective study, we highlight that P. vivax malaria is the most common Plasmodium among Latin American migrants, which is a matter of concern for disease control programmes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Geosentinel surveillance system, they have a higher risk of malaria and other vector-borne diseases in comparison with others travellers [ 25 ]. An American study showed that 90% of malaria’s diagnosis in the USA during 1997 was in people born in endemic areas [ 26 ]. This data are confirmed by a later study from the USA, which assessed that 64.5% of patients with malaria’s diagnosis were recorded in travellers born in endemic area visiting friends and relatives [ 14 ].…”
Section: Introductionmentioning
confidence: 99%